2007
DOI: 10.1109/jssc.2006.886578
|View full text |Cite
|
Sign up to set email alerts
|

An Organic FET SRAM With Back Gate to Increase Static Noise Margin and Its Application to Braille Sheet Display

Abstract: These developed circuit technologies achieved the practical 1.75-s operation to change all 144 Braille dots on Braille sheet display and will be essential for the future large area electronics made with OFETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 15 publications
(15 reference statements)
1
42
0
Order By: Relevance
“…These timeconstants are much shorter than reported by Guerin et al [16] and Takamiya et al [17], and comparable with those reported by Fukuda et al [18]. They are, however, longer than reported by Kumar et al [19] for cells in which the aspect ratios of access, driver and load TFTs were optimised.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These timeconstants are much shorter than reported by Guerin et al [16] and Takamiya et al [17], and comparable with those reported by Fukuda et al [18]. They are, however, longer than reported by Kumar et al [19] for cells in which the aspect ratios of access, driver and load TFTs were optimised.…”
Section: Resultssupporting
confidence: 83%
“…switchable resistive memory [11,12], floating gate memory devices [13] and memory transistors [14]. Also reported are organic versions of dynamic [15] and static [16][17][18][19] random access memory i.e. DRAM and SRAM respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show that by adjusting the top gate biases in dual gate inverters, the noise margin can be brought from a typical value of less than 1 to about 5 V. This drastic improvement will pave the way to the fabrication of large, complex and robust organic circuits. 13,14 We gratefully acknowledge technical assistance from T. Geuns and financial support from the Dutch Polymer Institute, project 624, and from the EC ͑Project BIODOT, NMP-TI-4-STRP 032652͒.…”
mentioning
confidence: 99%
“…With fl exible and stretchable batteries, [66][67][68][69][70] processors, 71 and memory [72][73][74][75][76][77] becoming available, more complex devices with good electrical properties can be achieved using only fl exible devices, enabling entire systems with mechanical fl exibility throughout.…”
Section: Integrated Circuits and Systems On Foils Designmentioning
confidence: 99%